A study on managing technical core competencies (an initial study) - Perez, Christopher (University of the Philippines Diliman, Technology Management Center, 2007)
Dramatic changes in organizations are occurring. A large proportion of these changes places an emphasis on the development and use of intellectual assets and the development of core competencies. The study proposes that core competencies are the result of a deliberate management strategy. In order to be supportive to this business strategy, the practice of business management, technology management, knowledge management and human resources management will have to undergo significant transformation. The key to this transformation consists in redefining the key concept of the job into a set of individual competencies and organizational units into core competencies architectures. Although it is widely accepted that alignment of core competencies with the wider corporate strategy is necessary, to date there have been few clearer statements on what a core competency strategy looks like and how it may be practically implemented. Often argued that current methods and techniques to accomplish this alignment are severely limited, showing no clear description on how the alignment can be achieved. In this study we examine the role of core competencies in the development of business and knowledge strategies. Viewing knowledge embedded in core competencies as a strategic asset, the study describes a case study of a local company to show how a company's core competencies were articulated and verified for embedding their inclusion in the overall strategy of the corporation. The study itself is representative of similar studies across a range of organizations using a novel method. Many companies have developed or adopted various core competency development and knowledge management (KM) initiatives to try to surface and differentiate what they do know from what they need to know and also identify the location of their knowledge gaps. Processes and tools that support efforts to capture knowledge are well known and widely used, such as expertise directories, intranets, communities of practice, knowledge audits, discussion forums, knowledge maps, post-project or after-action reviews, lessons learned banks, building and documenting knowledge based and expert systems, storytelling, benchmarking and the like. Although the importance of strategic alignment is well recognized, what is less understood is the practical means to determine what core competencies are strategically important and how these core competencies can be incorporated into the overall corporate strategy. For example, many suggests that companies may have unique ways of doing this, (itself a competitive advantage) and using different techniques such as SWOT analysis are applicable. Core competency management undertakings typically center on the core and competent people who embody and can apply their competencies in projects or other business activity settings, and often entail recording or abstracting from the traces of their contextualized activities. Such core competency development initiatives implicitly recognize the centrality of the competencies of individuals and groups in transacting the strategic aims of the organization at operational levels, and in potentially identifying the specific competencies, knowledge, skills and abilities that give comparative advantages. Rarely, however, are such initiatives directly linked to the overall corporate strategy and (often inappropriately) are typically designed and implemented through the organization's individual business units. A focus on the core competencies related to the overall strategic objectives may be more productive and useful to augment the competitive advantage of an organization. If organizations are centrally reliant on their core competencies for their survival, value and market leadership, their core competency and knowledge management strategies must be fully congruent with wider corporate strategy. A company's core competencies (Pralahad and Hamel, 1990) are the areas in which it has competitive strength and thus form a platform for its strategic thrusts. Not knowing or appreciating these means its strategies may fail and compromise proper valuation of a company's knowledge assets underlying the support, adaptation and maintenance of its activities. Core competencies are the "cognitive characteristics of an organisation, its know-how..." Core competencies are necessary part of a knowledge strategy which itself is part of the overall strategy, whether embedded or aligned. To give a sustainable strategic advantage, competencies should be valuable, rare, hard to imitate or substitute, and ideally will confer a dominating ability in their area. The theoretical literature on core competencies does not, however, generally relate their development to concepts of knowledge management operation, nor to strategy implementation. Nor, although recognising that some competencies more important than others, does it distinguish strategic from operational core competencies. We find it useful to differentiate these since the only way strategy can be realized is at the operational level, by competent people performing activities that achieve strategic goals. For this to occur, an explicit linkage between strategic goals and operational activity, between strategic core competencies and their implementation (and reciprocally between operational competencies and strategic objectives) must be articulated. Since contemporary thinking on strategy emphasizes ability to respond to environmental changes quickly at all levels rather than planning in a controlled environment, an embedded knowledge strategy will act as the medium through which these levels can be brought into alignment and allow for emergent strategy to be developed across the organization. We may asks the question "But how does a firm decide what set of operating-level initiatives would best meet its strategic goals?" and goes on to identify the "challenge of linking strategy with execution at the knowledge or competency level" by a focus on various activities around intellectual capital. As an open research question however, specific implementation guidance is not offered, and associated literature often notes only generic steps (identify strategic business drivers, determine business critical knowledge characteristics and locations, construct knowledge value chains and find competency gaps). Yet an organization's ability (or otherwise) to knowledgeably enact and leverage corporate processes and technologies is the essence of a strategic competency. In a view of strategy that is not purely top down, but is essentially enacted dynamically by the knowledgeable activity of people in the "middle", it is crucial to reify these competencies in relation to strategy formulation. Current tools do not go far enough in guiding this, nor do they provide explicit methods for systematic engagement at this level. This paper will describe a case study of a Philippine-based company and the development and mapping of its long-term corporate core competency development and knowledge strategy. Having identified the need to provide detailed guidance on identifying an organization's core competencies and to relate these effectively to knowledge strategy and overall corporate strategy, we outline processes that address this weaknesses and show how they can be implemented within more generic strategic planning processes. We illustrate these in the case study context to show how the organization systematically identified its core competencies, as well as determining the core competencies that are of strategic importance. In the process, learning that the company not only did not have the strategic competencies it thought it had, but that it had knowledge assets which it had not realized, provided the capability to explicitly incorporate the competencies into the overall corporate strategy. Finally, we conclude that this study had demonstrated a successful process of core competency development and knowledge strategy development and that the framework used is an appropriate vehicle to properly manage their core competency strategies.